Spotkania z literaturą. O dialogu międzykulturowym i kształtowaniu tożsamości nie tylko na godzinach polskiego (na przykładzie Eli-Saneli Katarzyny Pranić) .......... 151 - Łazarska, Danuta (Tożsamość na styku kultur: 4, 2021)
ENCOUNTERS WITH LITERATURE. ON INTERCULTURAL DIALOGUE AND IDENTITY FORMATION NOT ONLY DURING POLISH LESSONS (ON THE EXAMPLE OF ELA-SANELA BY KATARZYNA PRANIĆ)The author begins by considering the role of readers’ encounters with literature. She engages in a reflection on shaping readers’ identity and opening them to intercultural dialogue. She writes about the role of literature for children and young people in opening Polish philology students and their future pupils to intercultural dialogue and shaping the identity of both. She focuses on the presentation of Katarzyna Pranić’s novel Ela-Sanela as proposed reading, enabling the implementation of these tasks. She also presents the value of such preparation of candidates for teachers of Polish based on literary texts and students’ texts, being a testimony to the perception of literature.